2022
DOI: 10.1108/jfep-04-2022-0091
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Islamic finance on trade in insurance services in selected countries in the Middle East region

Abstract: Purpose Islamic finance is becoming a core part of the financial services economy in the Middle East countries. There is a strong likelihood that Islamic finance is also driving the expansion of trade in insurance services. However, research on Islamic finance’s effect on trade in insurance services is scant. This study aims to fill this gap by investigating if Islamic finance has promoted trade in insurance services. Design/methodology/approach This study adopts the gravity modelling framework and the panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
0
0
Order By: Relevance
“…Parallel to this growth, IF research has garnered increasing interest, yet it is still in a development phase, as indicated by Narayan and Phan (2017). The focus of earlier research includes performance analyses of Islamic banks (Alexakis et al, 2019;Johnes et al, 2014;Kablan and Yousfi, 2016;Mobarek and Kalonov, 2014;Wanke et al, 2016), investigations into their corporate governance system (Jan et al, 2023;Rashid et al, 2023;Toumi and Hamrouni, 2023) and studies on Islamic bond markets (Alam and Ansari, 2020;Azmat et al, 2014;Maghyereh and Awartani, 2016;Tiwari et al, 2023;Uluyol, 2023) and the Islamic insurance system (Al-Fori and Gani, 2022;Bekkin, 2007;Saharuddin et al, 2023). In addition, ethical issues in IF have been explored, with studies focusing on the ethical framework of Islamic financial institutions (Alziyadat and Ahmed, 2019) and the social responsibility roles of Islamic financial institutions (Hassan and Salma Binti Abdul Latiff, 2009;Kanapiyanova et al, 2022;Kotb Abdelrahman Radwan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Parallel to this growth, IF research has garnered increasing interest, yet it is still in a development phase, as indicated by Narayan and Phan (2017). The focus of earlier research includes performance analyses of Islamic banks (Alexakis et al, 2019;Johnes et al, 2014;Kablan and Yousfi, 2016;Mobarek and Kalonov, 2014;Wanke et al, 2016), investigations into their corporate governance system (Jan et al, 2023;Rashid et al, 2023;Toumi and Hamrouni, 2023) and studies on Islamic bond markets (Alam and Ansari, 2020;Azmat et al, 2014;Maghyereh and Awartani, 2016;Tiwari et al, 2023;Uluyol, 2023) and the Islamic insurance system (Al-Fori and Gani, 2022;Bekkin, 2007;Saharuddin et al, 2023). In addition, ethical issues in IF have been explored, with studies focusing on the ethical framework of Islamic financial institutions (Alziyadat and Ahmed, 2019) and the social responsibility roles of Islamic financial institutions (Hassan and Salma Binti Abdul Latiff, 2009;Kanapiyanova et al, 2022;Kotb Abdelrahman Radwan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%